2019
DOI: 10.1128/mbio.00837-19
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Emergence of Peptides That Confer Antibiotic Resistance

Abstract: The origin of novel genes and beneficial functions is of fundamental interest in evolutionary biology. New genes can originate from different mechanisms, including horizontal gene transfer, duplication-divergence, and de novo from noncoding DNA sequences. Comparative genomics has generated strong evidence for de novo emergence of genes in various organisms, but experimental demonstration of this process has been limited to localized randomization in preexisting structural scaffolds. This bypasses the basic req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 72 publications
1
44
1
Order By: Relevance
“…We expect that this proportion might rise above the 10% observed in this study (Fig. 3), a fraction that already far exceeds observations based on random sequences 17,18,55,80 , if emerging sequences were screened across additional conditions and wider ranges of expression levels. Hence, while emerging sequences show no evidence of encoding a useful protein product in the present state of the organism, they have the potential to do so in the future.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…We expect that this proportion might rise above the 10% observed in this study (Fig. 3), a fraction that already far exceeds observations based on random sequences 17,18,55,80 , if emerging sequences were screened across additional conditions and wider ranges of expression levels. Hence, while emerging sequences show no evidence of encoding a useful protein product in the present state of the organism, they have the potential to do so in the future.…”
Section: Discussioncontrasting
confidence: 51%
“…Beyond yeast, putative de novo genes with TM domains have also been characterized [51][52][53][54] . Furthermore, evidence suggests that the fitness-enhancing capacities of small TM proteins might extend to bacteria as well as to mouse 18,[55][56][57] . Finally, unannotated TM sequences may also be pervasively translated in bacteria, insects and mammals [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Neme et al's (2017) experiment was suitable for this purpose because it used a large library of peptides with diverse properties, and selected under relatively permissive conditions, simply for relative growth rates in the presence of peptide expression. In contrast, a study design such as that of Knopp et al (2019), who selected random peptides that rescue viability in the presence of antibiotics, is less suitable for our purposes because so few peptides, including harm-avoiding peptides, are viable. Neme et al's (Neme, et al 2017) study was also convenient because all peptides were the same length -65 amino acids with 50 amino acids of random sequenceallowing us to neglect length in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…by accidental expression of normally non-functional sequences that could confer a beneficial effect. Comparative genomics has provided many convincing examples of the de novo emergence of genes across distant organisms [ 9 13 ], but experimental demonstration of this process is limited [ 14 16 ]. Initial studies have shown that resistance genes can be isolated from random sequences, however these de novo genes likely have limited clinical significance due high associated fitness costs and their inferiority to naturally occurring resistance determinants [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomics has provided many convincing examples of the de novo emergence of genes across distant organisms [ 9 13 ], but experimental demonstration of this process is limited [ 14 16 ]. Initial studies have shown that resistance genes can be isolated from random sequences, however these de novo genes likely have limited clinical significance due high associated fitness costs and their inferiority to naturally occurring resistance determinants [ 16 18 ]. It remains unclear if and how de novo gene evolution contributes to the evolution of antibiotic resistance genes, but conceivably experimental selection of de novo resistance genes may allow the identification of possible resistance pathways that either have not yet emerged, or, more importantly from a medical perspective, are present but yet undetected in natural bacterial isolates.…”
Section: Introductionmentioning
confidence: 99%